Optimal Replacement of Capital Goods: The Early New England and British Textile Firm - Williamson, Jeffrey G. (Journal of Political Economy, 1971)
Economic historians have long been interested in the determinants of firm replacement policy under conditions of rapid technological development. This paper develops two models of replacement behavior–one with neutral and one with labor-saving technical change–under conditions of embodiment. Expressions for the optimal life of capital equipment are derived assuming environmental conditions consistent with the British and American textile sectors from the 1820s to the 1850s. The paper explores the influence of technical progress parameters, wages, interest rates, capital goods prices and output prices on the replacement decision. The paper concludes that tariff policy has had a significant impact on replacement and, further, that it helps shed considerable light on the divergent experience of these economies with the growth of industrial productivity.